2002
DOI: 10.1128/aac.46.4.1026-1031.2002
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin Pharmacokinetics and Efficacy in Uncomplicated-Malaria Patients Treated with Two Different Dosage Regimens

Abstract: The immediate efficacies of two oral dosage regimens of artemisinin were investigated in 77 male and female adult Vietnamese falciparum malaria patients randomly assigned to treatment with either 500 mg of artemisinin daily for 5 days (group A; n ‫؍‬ 40) or artemisinin at a dose of 100 mg per day for 2 days, with the dose increased to 250 mg per day for 2 consecutive days and with a final dose of 500 mg on the fifth day (group B; n ‫؍‬ 37). Parasitemia was monitored every 4 h. The average parasite clearance ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 22 publications
(27 reference statements)
3
55
0
Order By: Relevance
“…In comparisons of the AUCs of different doses in previous studies, the relative bioavailability after 4 to 7 days was between 0.13 and 0.29 (7,9,22,26,40,43). One study of African adults with malaria who received 500 mg of ART daily for 3 days and a single dose of mefloquine (42) measured ART in saliva and found that relative bioavailability was lower (0.45) only on the third day when mefloquine was given after the last dose of ART.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In comparisons of the AUCs of different doses in previous studies, the relative bioavailability after 4 to 7 days was between 0.13 and 0.29 (7,9,22,26,40,43). One study of African adults with malaria who received 500 mg of ART daily for 3 days and a single dose of mefloquine (42) measured ART in saliva and found that relative bioavailability was lower (0.45) only on the third day when mefloquine was given after the last dose of ART.…”
Section: Discussionmentioning
confidence: 95%
“…A number of published studies have evaluated the pharmacokinetics of ART in healthy adults (6,7,10,19,23,43) and adults with malaria (2,9,21,22,24,26,42), but only one has included children with malaria (40). In the latter Vietnamese study, 23 children aged 2 to 12 years were given 5 days of ART dosed according to body weight (approximately 10 mg) and 31 adults received 500 mg of ART daily for 5 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-dependent pharmacokinetics has been well described for artemisinin in healthy subjects and malaria patients (4,10), with a decrease in dose-normalized artemisinin concentrations over 5 days of drug administration due to autoinduction of metabolism (9,25). Declining plasma concentrations for artemether (29) and, less convincingly, for artesunate and dihydroartemisinin (14,35) have been reported following multiple doses.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may account for the differential efficacy of the primaquine treatment between sexes that could affect the efficacy of the drug reducing the intensity of infection. Many other reports in medical and veterinarian literature have identified host sex as a key factor affecting drug pharmacokinetics at two different levels, the absorption and the metabolism of drugs (Gordi et al 2002 ;Pinsonneault and Sadeé, 2003 ;Klein, 2004) although, in humans there are no differences in the kinetic parameters of primaquine between sexes (Elmes et al 2006). Also, other factors tightly related to sexual characteristics, such as hormone concentrations and genetic differences, may be involved in the influence of sex on drug pharmacokinetics (Pinsonneault and Sadeé, 2003).…”
Section: Discussionmentioning
confidence: 99%